A novel bundle adjustment method with additional ground control point constraint. Issue 1 (2nd January 2017) - Yan, Lei; Chen, Rui; Sun, Huabo; Sun, Yanbiao; Liu, Lei; Wang, Qiang
ABSTRACT: Bundle adjustment (BA) using parallax angle feature parameterization (ParallaxBA), has been recently reported to have better convergence and more accurate structure estimation in. However, ParallaxBA is a merely free-net BA model and is incapable of geolocating tie points in the global (geodetic) coordinate system. This study presents a novel BA method that incorporates Ground Control Points (GCPs) into ParallaxBA based on hybrid feature parameterization (ParallaxBA-GCP). Different from other BA methods based on feature parameterization using Euclidean xyz coordinates, the tie points in ParallaxBA are parameterized with three types of angles: azimuth, elevation and parallax angles. Therefore, the observation function of the tie points and that of GCPs were described with hybrid feature parameterization in the form of angles and xyz parameterization, respectively. The result of one real data set demonstrates that, when a poor initialization is given, ParallaxBA-GCP can converge within a very few iterations and rapidly triangulate high-quality tie points that satisfies the accuracy requirement of the aerial triangulation.